(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
This review article addresses the aspects inherent to the characteristics of organizational learning and exploitation and exploration, namely, its background, phases and types of learning. Likewise we will relate according to literature studies how organizations have the capacity to develop at the same time innovations that exploit their current learning and at the same time explore new opportunities that go beyond the present learning, where we determine it as organizational ambidexterity. Thus, it is concluded that organizational learning relates the learning of exploitation and exploration.